Rekonstruksi Peran Kepolisian dalam Pemenuhan Akses Keadilan bagi Tersangka pada Tahap Pra-Ajudikasi Berdasarkan KUHAP Baru - Dede Adi Supriyadi; Haidan Angga Kusumah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Indonesia’s Law No. 20 of 2025 on the Criminal Procedure Code replaces the 1981 framework and emphasizes suspects’ rights as a central element of legal reform. However, broad police coercive authority during the pre-adjudication stage still creates risks of procedural-rights violations due to limited operational standards, safeguards, and accountability mechanisms. This study aims to analyze and reconstruct the police role to ensure suspects’ access to justice is aligned with the principle of due process of law. This normative legal research applies statutory, conceptual, and case approaches. Legal materials were collected through library research and analyzed using qualitative-normative methods involving systematization, interpretation, evaluation, and prescriptive legal construction. The findings show that the New Criminal Procedure Code strengthens suspects’ protection through mandatory interrogation recording, legal aid notification, advocate assistance, minimum evidentiary requirements, restrictions on coercive measures, and expanded pretrial review. Nevertheless, several implementation challenges remain, including the lack of technical recording standards, weak early legal-aid referral mechanisms, and unclear factual parameters for suspect designation, arrest, and detention. This study proposes an integrated pre-adjudication reconstruction based on due process of law, requiring implementing regulations, structured police discretion, and preventive and corrective oversight mechanisms to ensure meaningful protection of suspects’ rights.